"Flexibility and Consistency": Qualitative Insights on Valuable Skills for Providers Working with Survivors of Child Sex Trafficking. Issue 3 (4th May 2023) - O'Brien, Jennifer E.; Jones, Lisa M.; Mitchell, Kimberly J.
ABSTRACT: Purpose: The commercial sexual exploitation of children (CSEC) is the commercial exchange of sex or sexual acts by an individual under the age of 18. Though many programs aim to serve youth who are (potential) victims of CSEC, it remains unclear what strategies and techniques are most helpful in engaging this population in treatment. Love146 is an anti-trafficking program with an established treatment specific for CSEC-impacted youth. This exploratory study sought to better understand the strategies and techniques that Love146 social workers, administrators, and staff use to facilitate engagement and healing among the children and youth they serve. Method: A total of 14 administrative and clinical staff at Love146 participated in 4 focus groups that were digitally recorded, transcribed verbatim, and coded using a content analysis approach. Results: Three distinct themes emerged, including the importance of using a trauma-informed approach, trustworthiness, and persistence. Discussion: There are many strategies and techniques that may aid service providers and administrators in engaging youth who have been impacted by CSEC.A full exploration into qualitative results, including implications for policy, practice, and research are provided.